Validity and invariance according to sex and age of the Paykel Scale of Suicide Ideation in Peruvian adolescents - Baños-Chaparro, Jonatan (2020)
Introduction: Suicidal ideation is the behavior of the individual linked to irrational thoughts about the life. At present, it is considered as the first step towards suicidal behavior and is mostly associated with teenagers. Method: 251 students between 12 and 18 years old participated (ME = 14.73, SD = 1.57) which responded the Paykel Suicide Scale (PSS) and sociodemographic data. Results: Factor analysis was performed confirmation of 2 unifactorial models, the first model did not present adequate adjustment rates, so which proceeded to the covariance of items 4 and 5, obtaining optimal results in the second model of the one-dimensional instrument. It was subsequently performed a third model of MIMIC invariance, where it was used as predictors to the variables of sex and age to the model previous, which allowed to determine the lack of difference between these categorical groups. Conclusion: It is determined that the PSS is a consistent and reliable test, which yields valid results in the Peruvian population, so you can have an instrument that evaluates suicidal ideation with referential parameters.